The Influence of Price, Product Quality, and Digital Marketing on Repurchase Intention of 'So Soft' (Environmentally Friendly) Detergent: The Role of Customer Loyalty as an Intervening Variable - Masjhur, Ahmad; Hermawan, Sigit; Abadiyah, Rifdah (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze the impact of price, product quality, and digital marketing on the repurchase interest of the environmentally friendly detergent 'So Soft,' with customer loyalty as an intervening variable. The research was conducted in Sidoarjo District, Sidoarjo Regency, with respondents aged 17-45 years. The research method used is quantitative, with data collection through a questionnaire distributed online via Google Forms, resulting in a sample of 100 respondents. Primary data collection in this study used a Likert Scale questionnaire distribution technique. Data analysis was conducted using SEM-PLS with SmartPLS software. The findings reveal that price, product quality, and digital marketing have a positive and significant effect on purchase interest, both directly and through customer loyalty as a mediating variable. This finding emphasizes the importance of an integrated marketing strategy that considers these three aspects to enhance customer loyalty and encourage purchase interest. The company should focus on competitive pricing, improving product quality, and implementing effective digital marketing strategies to build strong customer loyalty. High customer loyalty, in turn, will increase consumer purchase interest. The study also highlights the crucial role of customer loyalty as a bridge between the company's marketing strategies and consumer purchasing behavior, underscoring the importance of building long-term relationships with customers as a key to business success.